Arctic 2.0: How Artificial Intelligence Can Help Develop a Frontier. Issue 2 (2019) - Lin, Patrick; Allhoff, Fritz
Abstract: Technology has an outsized impact on the modern world; it is how we have tamed our frontiers. But that role is largely ignored when it comes to the Arctic frontier. Emerging technologies, especially AI, can enable desperately needed services and infrastructure—but they can also challenge ethics, law, and policy, as they usually do. For instance, autonomous icebreaker ships pose a dual-use dilemma since they can be used for both humanitarian and military purposes. As a lesson for other frontiers, this article will broadly introduce the potential role of AI in the changing Arctic and some of the ethical concerns that deserve attention before that future arrives.